Dietary intake of vitamins A, B, C, D and E and risk of islet autoimmunity and type 1 diabetes in genetically at-risk children: a prospective study from the DIPP birth cohort - Mattila, Markus; Haario, Peppi; Hakola, Leena; Takkinen, Hanna-Mari; Peltonen, Essi J.; Korhonen, Tuuli E.; Ahonen, Suvi; Ilonen, Jorma; Toppari, Jorma; Knip, Mikael; Veijola, Riitta; Niinistö, Sari; et al. (Springer Science and Business Media LLC, 2026)
Aims/hypothesis: In this prospective birth cohort study, we examined whether the dietary intake of A, B, C, D and E vitamins is associated with the risk of islet autoimmunity or type 1 diabetes in children who are genetically at risk for type 1 diabetes.
Methods: Data on vitamin intakes in the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) cohort study were available for 5674 children born between September 1996 and September 2004 in Oulu University Hospital or Tampere University Hospital. Diet was assessed using 3-day food records at the age of 3 and 6 months, and annually from 1 to 6 years. The primary outcomes were: (1) islet autoimmunity defined as repeated positivity for islet cell autoantibodies and at least one out of three type 1 diabetes-related biochemical autoantibodies or a diagnosis of type 1 diabetes; and (2) a diagnosis of type 1 diabetes.
Results: During the 6-year follow-up, 247 children (4.4%) developed islet autoimmunity and 94 (1.7%) developed type 1 diabetes. When adjusted for total energy intake, sex, HLA genotype and family history of diabetes, the intakes of retinol (HR 0.91; 95% credible interval [CrI] 0.86, 0.97 per 10 µg/MJ increase in intake), vitamin C (HR 0.70; 95% CrI 0.54, 0.90 per 10 µg/MJ) and vitamin E (HR 0.93; 95% CrI 0.89, 0.97 per 0.1 mg/MJ) were associated with decreased risk of islet autoimmunity and also with the risk of type 1 diabetes (retinol: HR 0.83; 95% CrI 0.74, 0.96 per 10 µg/MJ; vitamin C: HR 0.45; 95% CrI 0.23, 0.84 per 10 µg/MJ; vitamin E: HR 0.89; 95% CrI 0.80, 0.99 per 0.1 mg/MJ). The associations remained statistically significant after multiple testing correction for the risk of islet autoimmunity but not for type 1 diabetes. The association between retinol intake and islet autoimmunity risk was not significant when the 3-month age point, during which the child is primarily breastfed, was excluded. We observed a weak inverse association for vitamin D and islet autoimmunity, and no associations for B vitamins.
Conclusions/interpretation: High intake of vitamin C and vitamin E was associated with a decreased risk of islet autoimmunity.